Análise da política ambiental do ICMS-Ecológico em Mato Grosso - Silva, Elienai Carrias da (2020)
The current study aims to analyze the environmental compensation policy of the ICMS-e in Mato Grosso, considering the areas of UCs and the policy of transferring the ICMS to the municipalities of Mato Grosso. In this light, we used literature with theoretical approaches from traditional economics to ecological economics, as well as contemporary aspects of sustainability through compensation for ecosystem services. The study estimates the ability to offer ecosystem services in municipalities through the Standardized Concentration Index (ICN), highlighting those that are differentiated or specialized in ecosystem conservation. Another method used, the Conservation-Production Elasticity Index (IEcp) estimates the tendency of differentiated or specialized municipalities in conservation, given two possible scenarios, the first, in choosing to include new areas in conservation (IEcp<1), the second, the option for the production scenario (IEcp>1), which is calculated using the ICMS-e compensation function and the use of the ratio of the consolidated production index and the consolidated conservation index. Based on the estimates, the results show an average ICN (α) of 0.21 for UC areas, highlighting that 34.04% of the 141 municipalities are considered differentiated or specialized in offering ecosystem services, and that 22.7% are municipalities with ICN below the average, indicating that even having conservation areas, the capacity of ecosystem supply is of little relevance for acquiring incentives for available environmental resources. In another aspect, 19.15% of the municipalities stand out when obtaining representativeness of geographic spaces in capacity to offer ecosystem services above 1%, among which are Juína, Apiacás, Comodoro, Gaúcha do Norte and Querência. ICN estimates of ICMS-e demonstrate that the average ICN (α) is 0.72, and that approximately 29.36% of the municipalities are estimated to be differentiated or specialized, given the transfers of resources through the ICMS. In this dynamic, 38.94% of the municipalities are estimated as areas of conservation effort (QL>1), 23.62% of the municipalities obtain potential in environmental concentration (IIH>1), and 26.95% have relative importance of services ecosystems in their territories. With the results of the municipalities considered differentiated or specialized in ecosystem supply, the IEcp estimates that on average 75.2% obtained a tendency to use the new areas of land in ecosystem conservation, considering that they are scenarios that do not take into account the qualitative nature of each area. The IEcp estimate also highlights that the lower the municipality's participation in the transfer of ICMS, the greater the tendency to opt for the inclusion of new areas in ecosystem conservation. Of the 32 municipalities with the lowest participation (up to 0.5%), about 90.6% tend to ecosystem conservation, of the municipalities with participation between 0.51% to 1% in the ICMS, 80% would also have a tendency for the scenario of inclusion of areas in ecosystem conservation. The correlation of the IEcp estimate to the average land price shows that, in general, the municipalities with the lowest value in land prices tend to choose to conserve the new areas, but there are also those with high land prices that have obtained trends in ecosystem conservation. The estimated results demonstrate the importance of conservation areas for the sustainable development process of the territory of Mato Grosso, as well as environmental policies and the need to understand the current conditions of local ecosystem conservation.